Cybersecurity in Latvia : Forging Resilience Amidst Emerging Threats - Mihails Potapovs; Kate E. Kanasta (Routledge, 2026)
Drawing on expertise from professionals, government officials, and academics, this book uncovers the proactive measures taken by Latvia to build resilient cybersecurity capabilities.The work offers a comprehensive exploration of Latvia's cyber domain, structured around three overarching themes: the ecosystem, its processes, and future perspectives. In doing so, it takes readers through the intricacies of Latvia's cybersecurity landscape and provides a nuanced understanding of its strengths, challenges, strategic considerations, and broader implications. One of the key contributions of the work lies in its exploration of Latvia's cybersecurity strategies and resilience. By delving into the nation's policies, collaborations, and technological advancements, this book uncovers how Latvia has proactively addressed cyber threats, emphasising the importance of tailored approaches for smaller countries in building robust cybersecurity defences. Highlighting the importance of studying cybersecurity in smaller nations, this book stresses Latvia's contributions to global cybersecurity efforts as an EU and NATO member. The volume advocates for innovation and collaboration, emphasising their crucial role in securing a digital future for nations worldwide.This book will be of much interest to student of cybersecurity, Baltic politics, EU politics, global governance, and International Relations.The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-Share Alike (CC-BY-NC-SA) 4.0 license.